2022
DOI: 10.1186/s12912-022-00933-y
|View full text |Cite
|
Sign up to set email alerts
|

Influence of emotional intelligence on the clinical ability of nursing interns: a structural equation model

Abstract: Background Internship is a critical period during which nursing students develop clinical skills and establish professional attitudes. Requirements for nursing interns are evolving with the development of medicine and the transformation of teaching models. The emotional intelligence (EI) of nursing students has an influence on their clinical performance. This study aimed to investigate the impact of EI on the clinical ability of nursing interns. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“… Tajpreet and Maheshwari (2015) revealed a favorable relationship between EI and self-esteem ( r = 0.64) in a study of youths in Faridkot, Punjab. Assessing the relationship between EI and self-esteem among nursing students is essential for promoting student well-being, preparing for clinical practice, enhancing patient-centered care, facilitating personal and professional growth, informing educational interventions, and contributing to research and scholarship in nursing education and practice ( Dou et al, 2022 ). Nurturing EI skills among nursing students can positively impact their self-esteem, ultimately benefiting both their personal development and their effectiveness as healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“… Tajpreet and Maheshwari (2015) revealed a favorable relationship between EI and self-esteem ( r = 0.64) in a study of youths in Faridkot, Punjab. Assessing the relationship between EI and self-esteem among nursing students is essential for promoting student well-being, preparing for clinical practice, enhancing patient-centered care, facilitating personal and professional growth, informing educational interventions, and contributing to research and scholarship in nursing education and practice ( Dou et al, 2022 ). Nurturing EI skills among nursing students can positively impact their self-esteem, ultimately benefiting both their personal development and their effectiveness as healthcare professionals.…”
Section: Discussionmentioning
confidence: 99%
“… 26 A similar situation was also found in China, where students’ emotional intelligence influences their clinical performance. 27 In a study with medical residents during the pandemic, researchers found that emotional intelligence partially protects against burnout and the well-being of residents during their residency. 28 Our study revealed that the variable emotional intelligence was associated with the variable concern about returning to face-to-face classes.…”
Section: Discussionmentioning
confidence: 99%
“…The COVID-19 pandemic has posed a major challenge to the mental health and emotional wellbeing of the population, and the numerous psychological consequences caused by the pandemic can be seen in the increased demand for care. Available evidence indicates that soft skills training provides tools for coping with such disturbances and improving adaptation and resilience [ 62 , 63 , 64 , 65 ]. Recent studies have observed the benefits of IE during the pandemic, including reduced intensity of negative emotions and lower prevalence of anxiety and depression [ 66 , 67 ].…”
Section: Discussionmentioning
confidence: 99%